Implementasi Analisis Forecasting Penjualan Ekspor Copra Dengan Metode Time Series Pada CV. DATY International Di Tembilahan - Yoga Winanda, T.; Akbar, Rahmad; Rahmayani, Merlia; Yetti, Dzulhijjah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Forecasting is an estimate of something that has not happened or will happen in the future. Forecasting is a very important element in decision-making, because the effectiveness of a decision generally depends on several factors that we cannot see when the decision is made. In mathematics, the part that can be used in forecasting is simple regression with linear trend analysis using the least squares method. The purpose of writing this thesis is to predict the number of export sales of copra and coconut shell through Linear Trend analysis and application using the Least Squares Method.